2003
DOI: 10.1002/asi.10283
|View full text |Cite
|
Sign up to set email alerts
|

The user‐subjective approach to personal information management systems

Abstract: In this article we suggest a user-subjective approach to Personal Information Management (PIM) system design. This approach advocates that PIM systems relate to the subjective value-added attributes that the user gives to the data stored in the PIM system. These attributes should facilitate system use: help the user find the information item again, recall it when needed, and use it effectively in the next interaction with the item. Driven from the user-subjective approach are three generic principles which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 16 publications
2
81
0
2
Order By: Relevance
“…according to projects), however, current design discourages them from doing so (by suggesting format-related storage). The project fragmentation problem has already been mentioned in the User Subjective approach to PIM systems design [3], but hasn't been empirically studied so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…according to projects), however, current design discourages them from doing so (by suggesting format-related storage). The project fragmentation problem has already been mentioned in the User Subjective approach to PIM systems design [3], but hasn't been empirically studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the user-subjective approach [3] we propose a different kind of solution -the single hierarchy solution -in which all project-related information items are stored in the same folder regardless of their format (see also [11]). This solution is also derived from the reported empirical data: users tend to manage their personal information in a project-oriented way whenever design suggests it (documents of different formats in the same project folder), but they store items related to the same project in different locations when interface design reinforces such fragmentation.…”
Section: The Single Hierarchy Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…La existencia de una mayor cantidad de información electrónica en distintos dispositivos y soportes genera algunos problemas para el consumidor por la dificultad de su gestión (Bergman et al, 2003). Una mayor carga informativa exige al usuario una gestión y control de la información que permita el archivado y su recuperación de manera eficiente (Franganillo, 2009).…”
Section: Descripción De La Investigaciónunclassified
“…It has also be demonstrated that people are more likely to remember words or concepts if they have structured them or labelled them in a way that is personally significant. These evidences endorse a user subjective approach to PIM, which advocates that users should be able to assign subjective, value-added attributes to information objects to help facilitate retrieval [Bergman et al, 2003]. The reviewed literature seems to indicate that improved facilities for personalisation would encourage improved recollection and therefore enhance retrieval.…”
Section: Theme 2: Multi-modal Access To Information Objectsmentioning
confidence: 99%